Incorporating Real-World Applications into Chemistry Curriculum: Enhancing Relevance and Student Engagement - Choriqulova Dildora O`'tkirjon qizi; Pardayev Ulug'bek Xayrullo o'g'`li; Kosimova Xurshida Rajabboyovna, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Integrating real-world applications into the chemistry curriculum is a pivotal endeavor to enhance relevance and student engagement in science education. This article delves into the rationale, strategies, and outcomes associated with the incorporation of real-world contexts in teaching chemistry. By synthesizing empirical research, theoretical frameworks, and practical experiences, this paper examines the impact of real-world applications on student motivation, conceptual understanding, and career readiness in chemistry. Furthermore, it explores diverse approaches to infusing real-world relevance into the chemistry curriculum, encompassing the selection of authentic contexts, the design of contextualized learning experiences, and the integration of interdisciplinary connections.